2011
DOI: 10.1159/000335598
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activities of Nisin Alone or in Combination with Vancomycin and Ciprofloxacin against Methicillin-Resistant and Methicillin-Susceptible <i>Staphylococcus aureus</i> Strains

Abstract: Background: We investigated the in vitro activities of nisin alone or in combination with vancomycin and ciprofloxacin against methicillin-resistant (MRSA) and -susceptible Staphylococcus aureus (MSSA) strains. Methods: The minimum inhibitory concentrations were determined by microbroth dilution technique. Antibiotic combinations were assessed using the checkerboard technique. The time-kill curve method was used for determining the bactericidal activity of nisin alone and in combination. Results: For both MSSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…CHX has synergism with hydrogen peroxide against Streptococcus sobrinus, Streptococcus faecalis, and Staphylococcus aureus [35]. VAN has a low degree of synergism with the antibacterial nisin against some S aureus strains [13]. Also, VAN has synergism with sulfamethoxazole/trimethoprim and rifampin against some Staphylococcus strains; however, when combined with imipenem and other drugs, VAN has synergistic effects against a broader range of methicillinresistant, coagulase-negative, and biofilm forms of Staphylococcus [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…CHX has synergism with hydrogen peroxide against Streptococcus sobrinus, Streptococcus faecalis, and Staphylococcus aureus [35]. VAN has a low degree of synergism with the antibacterial nisin against some S aureus strains [13]. Also, VAN has synergism with sulfamethoxazole/trimethoprim and rifampin against some Staphylococcus strains; however, when combined with imipenem and other drugs, VAN has synergistic effects against a broader range of methicillinresistant, coagulase-negative, and biofilm forms of Staphylococcus [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing resistance against Staphylococcus aureus strains, new combinations of antibiotics are requested [39,40]. …”
Section: Discussionmentioning
confidence: 99%
“…The rise of multidrug resistance in a variety of bacteria has prompted renewed interest in the development of novel antimicrobial agents [17]. Previous studies have showed that ulifloxacin, the active metabolite of prulifloxacin, had greater penetration within bacteria compared to levofloxacin, ciprofloxacin or gatifloxacin [18,19], and showed in vitro activity similar to or greater than ciprofloxacin and other fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%